Secondary ametropia retreatment with flap lifting performed long after LASIK surgery: a clinical case - N. V. Khodzhabekyan; A. T. Khandzhyan; A. V. Ivanova; A. S. Sklyarova; I. V. Manukyan (Российский офтальмологический журнал, 2023)
Purpose: to present a clinical case of secondary ametropia retreatment with flap lifting, which was performed long after a LASIK surgery.Material and methods. A female patient who experienced a regression of the refraction effect after a LASIK surgery, received a flap lifting with keratoablation 18 years after the primary LASIK surgery. 8 days following this procedure, the patient developed a complication, namely an epithelial ingrowth. Another flap lifting procedure was performed and the epithelial ingrowth was removed.Results. The expected refractive effect was achieved with binocular hypocorrection as planned.Conclusion. A repeated flap lifting undertaken 3 years or more after the first LASIK or FemtoLASIK surgery increases the risk of a complication — an epithelial ingrowth into the space under the flap. To avoid the complication in such cases, the retreatment by PRK is preferable. Scarification and elimination of the in-grown epithelial should be performed early after the surgery.